The Impact of Distributed Leadership on Teacher’s Job Satisfaction - Alam, Syamsir; Badeni, Badeni; Danim, Sudarwan; Kristiawan, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Teacher job satisfaction is an important factor in improving the quality of education. This research aims to examine the impact of distributed leadership on teacher job satisfaction. Distributed leadership is an approach where leadership responsibilities are shared among team members, rather than centered on one individual. This research uses a qualitative approach with a literature study method. The research results show that distributed leadership has a positive and significant influence on teacher job satisfaction. Factors that contribute to teacher job satisfaction include participation in decision making, collaboration between teachers, and professional support. In addition, this research found that distributed leadership can improve communication and coordination among team members, which ultimately has a positive impact on teacher job satisfaction. The conclusion of this research is that the application of distributed leadership in the education system can increase teacher job satisfaction. Therefore, educators and school administrators need to consider this approach in managing their teacher teams to create a better work environment and improve the quality of education